The Impact Of Pesticide Residue Accumulation On The Reduction Of Blood Cholinesterase Enzyme Levels In Dragon Fruit Farmers In Karo Land - Radina Yuni Mahesa Ginting; Sanna Kamisna Royani Purba; Mira Hastari Ginting; Atri Gustiana Gultom (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Pesticide use has a negative impact on dragon fruit farmers. According to the World Health Organization (WHO), an estimated 1-5 million people experience pesticide poisoning annually, with a mortality rate of 220,000 deaths. Individuals experiencing pesticide poisoning will have low cholinesterase levels. This decreased enzyme activity can lead to nervous system disorders, poisoning, and even death. This study aimed to determine the effect of pesticide accumulation on the decline in cholinesterase enzyme levels among dragon fruit farmers in Berastepu Village, Tanah Karo. Blood samples were examined at the MCI Indonesia Clinical Laboratory. A descriptive approach was used in this study, with blood samples collected from dragon fruit farmers. The results showed that 11 farmers had normal cholinesterase levels, while 4 farmers had abnormal levels. The average values ​​were normal (170.0-420 U/L) and abnormal (<170.0-420 U/L). The conclusion of the study with 15 samples was the cholinesterase levels in farmers who were exposed to pesticides 1-3 times a week with an age range of 31-40 years and 41-50 years.